Topology Optimization of a Composites Frame Structure considering ply orientation for MALE UAV - I B Wiranto; S O Saraswat; I R Alfikri; Chairunnisa; A Aribowo (Jurnal Sains Materi Indonesia, 2022)
This research employs the Finite element method to optimize the frame structure of a Medium Altitude Long Endurance (MALE) Unmanned Aerial Vehicle (UAV). The material used in this study is a unidirectional carbon fiber stacked in a specific sequence. The topology optimization process is conducted to achieve a lightweight structure whilst maintaining its integrity. The design constraint is set to reduce 50% weight and minimize the strain energy. The benchmark phase was performed while considering a previously done study to validate the proposed method. The results of this study have successfully reduced 34% (0.581 kg) weight of frame structure. First failure predicition study using Hashin criterion, shows the first failure occurred in the matrix of Ply-2 at 9000 N.